Houses of Horror Or Magical Kingdoms? Past Times Revisited With Miguel Ángel Asturias, Carlos Fuentes And Julio Cortázar - Jaeck, Lois Marie (CIENCIA ergo-sum, 2017)
In the three short stories to be examined, Miguel Ángel Asturias, Carlos Fuentes and Julio Cortázar incorporate Pre-Colombian beliefs and customs into colonial and post-colonial Latin American reality. Their fiction a mergers of “past" and "present" insinuate the reversibility/ambiguity of dreams/representation with physical reality. They thus recognize the authentic presence of Pre-Columbian culture in contemporary Latin American societies and put into question the validity of European North American materialism.